Future Compas Remove Career Confusion : Implementation of the "Future Compass" Workshop in Charting the Path to Success Vocational High School Students in the 5.0 Era.: Planning careers for vocational school students crucial - Sulis, Sulistianingsih; Salamah , Toriqotus; Permana , Hara; Nurodin (Sociocouns: Journal of Islamic Guidance and Counseling, 2026)
Planning careers for vocational school students crucial in the middle challenge Industrial Revolution 4.0 and the Era of Society 5.0, however Lots student Still face confusion direction consequence lack of assessment innovative and low awareness self . Research This aim analyze impact transformative from the "Future Compass" Workshop on motivation , awareness self , and quality planning career students of Muhammadiyah Larangan Vocational School, as response to crisis direction career . Research This use Approach Qualitative Descriptive Interpretive with Triangulation Method that combines Observation Participatory , Youth Mapping ( technique) visual and narrative reflections ), and interviews Reflective Deep to participants . Data processed through reduction , categorization thematic , and interpretation phenomenological For understand the internal transformation process . Research result show impact positive significant on participants . Participatory reflective method succeed grow motivation intrinsic and consciousness a better self high , shifting focus participant from weakness to potential self ( such as skill technical and entrepreneurial ). As many as 71.4% of participants show intention strong For change behavioral intention and clarity objective a better life directed . However , identified existence gap critical : (1) Gap of Ambition vs Action, where ideals tall No in harmony with effort term short that is still passive ; and (2) Person-Environment Fit Gap, marked by inconsistency between interests ( hobbies ) and choices career , which indicates the need exploration deep according to Holland's Theory. It is concluded that guidance career structured , especially through method participatory like Youth Mapping, very effective in increase ability vocational school students for planning and managing track career they in a way adaptive and sustainable .